Young's moduli of sputter-deposited NiTi films determined by resonant ultrasound spectroscopy: Austenite, R-phase, and martensite. (May 2015) - Thomasová, Martina; Sedlák, Petr; Seiner, Hanuš; Janovská, Michaela; Kabla, Meni; Shilo, Doron; Landa, Michal
Abstract : Young's moduli of 3 μm thick NiTi films sputter-deposited on silicon wafers are determined by resonant ultrasound spectroscopy. Three samples with different transition temperatures are studied; for each sample, the evolution of Young's modulus is obtained in a thermal cycle covering the austenite  →  R-phase  →  martensite transition sequence. The results prove that the smallest Young's modulus is attained for the R-phase, and both austenite and martensite exhibit pronounced softening towards the transition temperatures.